Improved Methodology for Mobile Commerce Applications - A., Hameed; Oudah, Ali A. (SERSC, 2014)
Agile based development methodology for mobile commerce applications (ADMMC), which is based on agile development framework, contains integration of essential factors in each phase of systems development life cycle of mobile commerce applications as wel l as guidelines to follow for conducting activities in the application development, including specific models, tools, and techniques. This paper aims to present the evaluation of ADMMC which assess its applicability and practicality. In this evaluation app roach, a mobile commerce application prototype were implemented by the two teams of developers, the first team used ADMMC while another team used the traditional waterfall development. The evaluation results showed two essential outcomes. Firstly, it was f ound that ADMMC is applicable as it can be used to create the intended system, mobile commerce applications in this case. Secondly, it showed that ADMMC is practical as when comparing to the traditional waterfall development by using the 11 measurements sp ecified, it exposed more benefits to the development process.